The Role of Academic Hope and Emotion Regulation on Psychological Well-being in Students - Nur, Nurhidaya; Simatupang, Gabriela Dyan; Nugraha, Dwi Yan (Journal of Educational, Health and Community Psychology, 2025)
Academic pressure experienced by students can impact their psychological well-being. This study aims to examine the influence of academic hope and emotion regulation on psychological well-being in students. This research employs a quantitative approach with a cross-sectional design, involving 152 respondents selected through convenience sampling. All variables were measured using a Likert scale and analyzed using hierarchical multiple regression with R (v4.4.2) and RStudio (v2024.12.0+467). The results indicate that academic hope significantly influences psychological well-being (B = 0.68, p < 0.001). Additionally, emotion regulation also contributes to enhancing students’ psychological well-being (B = 0.58, p < 0.001). These findings highlight the crucial role of academic hope and emotion regulation in supporting students' psychological well-being. The implications of this study emphasize the need to strengthen academic hope and emotion regulation within educational settings to optimize students' psychological well-being.